Utilization of Treated Malaysian Local Bentonite For Drilling Mud Material Cost Saving - Irawan, Sonny; Samsuri, Ariffin (2002)
Based on the result of Geological Survey Department Malaysia investigation, the bentonite resource in Sabah is huge. In order to reduce the overall cost in oilwell drilling and completion, the development of Sabah bentonite as drilling mud material has been initiated. Mineralogically of the samples were characterized as low grade Ca-Mg smectite. The dominant gangue mineral is ferrous with small amounts of kaolinite, quartz, illite, muscovite and hematite. Iron is present as magnetite and as amorphous oxides and hydroxides. Characterization of these samples indicated that the bentonite response for Na-exchange was poor while their hydration, plastic and rheological properties were inferior to those of reference bentonite (WY-BEN). The sample was processed by crushing followed by aero cyclone to optimum produced pre-concentrates, which were extracted with diluted oxalic acid. Application of such simple flow sheet effectively removed the majority of the associated ferrous ion. These concentrates were further refined by a series of organic acid prior to their evaluation as industrial bentonite. The mineralogy, chemical and physical properties analysis of final concentrates successfully match the required specifications for drilling mud industrial material. Utilization of this bentonite, after their extracting, can represent a value added to Malaysian economy (60.71% cheaper) by minimizing the imported bentonite used by oil and gas industry.